A Study on the Performance of Fri Skyline Crane in West Bengal - Mitra, S. K.; Sood, K. G. (Indian Forester, 1978)
The FRI Long Distance Skyline Crane was designed by the Logging Branch of F.R.I. and Colleges and fabricated locally making use of all indigenous components. The machine was subjected to extensive field trial for uphill extraction of timber in the inaccessible hill forests of Darjeeling district of West Bengal for nearly a year. Thereafter a detailed time and cost study was conducted at Luleygaon to find out its suitability, efficiency and economics of operation. The machine has shown a promising result particularly in view of the fact that this was the maiden attempt of the branch in designing and fabrication of such an equipment. Apart from the advantages that are inherent in an indigenous machine the performance of this machine with regard to its hauling capacity, hourly working cost and the cost of aerial transportation of logs compares favourably with similar equipments imported from foreign countries. The time and cost study also identified the scope and areas of improvements in the existing machine.